Importance Of Rogamarga & Its Crucial Role In The Manifestation Of Vyadhi (Disease) - Patel, Ramnarayan; Kande, Aradhana (International Research Journal of Ayurveda & Yoga, 2020)
The subject Rogamarga (disease pathway, seat, locale, the channel of diseases) is a unique contribution of Ayurved. Rogamarga can be defined as the actual pathway, mode or manners disease progresses and it plays a vital role in the samprapti janana. It is also an indication of how the disease is going to take place. Thus all conditions like occurrence, progress and recurrence of the disease depend on rogamarga. The subject Rogamarga indicates a relationship between different tissues and organs in a unique way. The knowledge of Rogamarga helps us to understand the dosha gati, the disease process in terms of manifestation and management (chikitsa). This review article aims to focus on the importance of Rogamarga and its role in the manifestation of vyadhi (disease). This conceptual study is helpful in the management of various progressive chronic diseases.